Students’ Self-Efficacy of Nicenet in EFL Classroom - Anita Rezki (Langkawi: Journal of The Association for Arabic and English, 2017)
This study attempts to measure students’ Self Efficacy in Nicent in EFL Classroom and to investigate whether or not there was any difference between male and female students. This study adopted a mixed method. Data gathered through questionnaire, interview and relevant documents. The study was conducted at the English Language Education study program, in Halu Oleo University. Fifty students participated in this study by filling out a questionnaire and 8 students were interviewed to obtain more information related to their response in the questionnaire. Findings of the study indicate that students’ self-efficacy were categorized into high level and medium level. Regarding differences between male and female’s self-efficacy in using Nicenet, the result of this study revealed no significant differences among them.